An experimental investigation of hydrodynamics of a fixed OWC Wave Energy Converter. (15th April 2016) - Ning, De-Zhi; Wang, Rong-Quan; Zou, Qing-Ping; Teng, Bin
Highlights: The hydrodynamic performance of a fixed OWC device is experimentally studied. There exists a critical wave slope at which hydrodynamic efficiency reaches the maximum. Slope angle has little influence on the resonant frequency. The water motion inside the chamber is highly dependent on the relative wave length λ / B . Abstract: The hydrodynamic performance of a fixed Oscillating Water Column (OWC) wave energy device under various wave conditions and geometric parameters was tested experimentally in a wave flume. The measured water surface elevation at the chamber center, the air pressure in the chamber of the OWC device and the hydrodynamic efficiency are compared well with the published numerical model results in Ning et al. (2015). Then the effects of various parameters including incident wave amplitude, the chamber width, the front wall draught, the orifice scale and the bottom slope on the hydrodynamic efficiency of the OWC device were investigated. It is found that the opening ratio ε ( ε = S 0 / S, where S 0 and S are the cross-sectional areas of the orifice and the air chamber, respectively) has a significant influence on the maximum hydrodynamic efficiency of the OWC device. The optimal efficiency occurs at the opening ratio of ε = 0.66%. Although bottom slope has little influence on the resonant frequency, the optimal hydrodynamic efficiency increases with the increase of bottom slope. A proper bottom slope can provide a work space in the OWC chamber almost independent on the sea wave conditions. The spatial variation of the water surface inside and outside the chamber was also examined. And the results indicate that the water motion is highly dependent on the relative wave length λ / B (where λ is the wave length and B is the chamber width). Seiching phenomenon is triggered when λ / B = 2 at which the hydrodynamic efficiency is close to zero.